Cannabidiol: brief compilation over a versatile molecule (Research, Society and Development, 2021)
Cannabis sativa has been applied for medicinal purposes for thousands of years. Cannabidiol is the main non-psychotropic compound in Cannabis sativa, and has its therapeutic effect extremely linked to the central nervous system, presenting pharmacological properties with great potential for the treatment of several pathologies. The aim is to identify and relate the therapeutic effects of cannabidiol in medicine, focusing on its therapeutic potential in epilepsy, autism, Parkinson's disease, Alzheimer's disease, oncological diseases, and chronic pain. In addition to presenting a brief history of cannabidiol and its chemical and pharmacological properties acting on the Central Nervous System. Integrative literature review, where articles were reviewed in Portuguese and English, based on PubMed, Scielo and Public Agencies. In 1960, the chemical structures of the main components of cannabis were identified, characterizing cannabidiol as a cannabinoid, which binds to cannabinoid receptors throughout the human body, known as CB1 and CB2. The endocannabinoid system, described in 1990, further demonstrated the therapeutic properties of cannabidiol, elucidating its neuroprotective, antiepileptic, anxiolytic, antipsychotic, anti- inflammatory, anti-tumor, antioxidant, and anticonvulsant properties. Cannabinoids may, in the future, be an important therapeutic option in the treatment of Parkinson's and Alzheimer's diseases, epilepsy, autism, neoplasms and still acting in the relief of pain. This is due to the absence of psychoactive effects and cognition, safety, good tolerability, clinical trials with positive results and the wide spectrum of pharmacological actions.